Klasifikasi Semantis Kata Penyukat Bahasa Mandarin dan Bahasa Indonesia - Irsyadi Shalima; Yuniarto Hendy; Rangga Asmara (TRANSFORMATIKA, 2019)
This brief research focuses on the semantic classification of measure words in Mandarin and Indonesian as both have the unique characteristic. By using contrastive methods, the measure words in both languages are compared and explained the similarities and differences. The results show that both languages have semantic classifications of the general measure words, national and international standards, containers, indeterminate numbers, a unity of objects, pairs, parts, humans, animals, plants, buildings, vehicles, shapes and distances. Although in general there are similarities, Mandarin has more measure words and is more detailed in classifying things.